Structural Equation Model for Creating Institutionalization Through the Implementation of the Department of Highways’ Digital Government Policy - Sutaveepramochanon, Nattanun; Chotchakornpant, Kasemsarn (Hatyai Academic Journal, 2025)
This research aims to study the causal relationship path of variables that influence the creation of institutional solidarity in the implementation of digital government policy of the Department of Highways. Additionally, it intends to confirm the elements of building institutional solidarity through mobilization factors and deliverer implementation through studying the implementation of digital government policy by the Department of Highways. This research used the structural equation technique to analyze data collected from 465 civil servants who were regular employees and government employees under central agencies. The results of the study using the structural equation modeling (SEM) analysis tool with the AMOS program found that the overall model is consistent with the empirical data when /df = 4.995, CFI = 0.966, TLI = 0.952, RMSEA = 0.093, RMR = 0.015. The factor with the most effect on the creation of institutional solidarity in adopting implemented digital government policies of the Department of Highways is the mobilization variable (Mobi) (TE = 0.956) which was statistically significant at the 0.001 level, while the practice variable (Demp) was found to have a minor influence (TE = 0.266). For the variance of each outcome variable, namely, the practice variable (Demp) and the institutional solidarity variable of policy implementation (Inst), it was found that the former was predicted as 84.7 percent of the variance from the mobilization variable (Mobi) (R2 = 0.847), and the latter was found to be predicted together with 92.4 percent of the shared variance from the mobilization variable (Mobi) and the practice variable (Demp) (R2 = 0.924). The results indicated that all three latent variables were suitable, and the measurement model was consistent with empirical data. In addition, as civil servants from the Department of Highways under central agencies are aware of mobilization, and perception of practice, this will directly affect the creation of institutional solidarity in implementing digital government policies.